Polymeric Nanoparticle Associated with Ceftriaxone and Extract of Schinopsis Brasiliensis Engler againstMultiresistant Enterobacteria - Oliveira, Maisa Soares de; Oshiro-Junior, Joao Augusto; Sato, Mariana Rillo [UNESP]; Conceicao, Marta Maria; Dantas Medeiros, Ana Claudia (Mdpi, 2020)
Bacterial resistance has become an important public health problem. Bacteria have been acquiring mechanisms to resist the action of antimicrobial active pharmaceutical ingredients (API). Based on this, a promising alternative is the use of nanotechnology, since when the systems are presented in nanometric size, there is an increase in the interaction and concentration of the action at the target site improving the activity. Thus, this study aims to develop a polymeric nanoparticle (PN) composed of chitosan and hydroxypropylmethylcellulose, as an innovative strategy for the administration of an association between ceftriaxone and extract ofS. brasiliensis, for the treatment of Enterobacteriaceae. From a Box-Behnken design, nanoparticles were obtained and evaluated using the DLS technique, obtaining the particle size between 440 and 1660 nm, IPD from 0.42 to 0.92, and positive charges. Morphological characteristics of PN by SEM revealed spherical morphology and sizes similar to DLS. Infrared spectroscopy showed no chemical interaction between the components of the formulation. The broth microdilution technique evaluated their antimicrobial activity, and a considerable improvement in the activity of the extract and the API compared to the free compounds was found, reaching an improvement of 133 times in the minimum inhibitory activity CRO.
Keywords: bacterial resistance; Enterobacteriaceae; chitosan; HPMC